Why do Chinese firms cross-list in the United States? - Peng, Mike; Blevins, D. (2012)
An interesting aspect to study the convergence of corporate governance is cross-listing. Cross-listing is when a company lists its shares on more than one stock exchange. In recent decades, there has been a drastic increase in cross-listing. Firms from around the world have sought to list their shares in the US. China, with its burgeoning economy, provides a natural starting point in developing a theoretical framework for understanding why firms cross-list in the US. We contribute to the strategy and management literature by using an institution-based view in developing a theoretical framework for understanding the phenomenon of why some Chinese firms cross-list in the US.